PENGARUH MODEL PEMBELAJARAN GENERATIF TERHADAP HASIL BELAJAR MAHASISWA BERDASARKAN STUDENT’S RESPONSE ATTITUDE PADA MATA KULIAH MEDIA PEMBELAJARAN - ZINNURAIN, ZINNURAIN (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2024)
This research aims to measure the extent of the influence of the Generative Learning Model on Student Learning Outcomes Based on Student's Response Attitude in the Odd Semester Learning Media Course for the 2023/2024 Academic Year. The method used was quasi-experimental with a 2 x 2 treatment by level design. The research hypothesis was tested using two-way analysis of variance (ANOVA). The research results showed that; The learning outcomes between the group of students who were given the generative learning model were higher than the group of students who were given the expository learning model and there was an interaction effect between the learning model and students' attitudes towards the Learning Media course on the learning outcomes of the Learning Media course. In the group of students who have a positive attitude, the learning outcomes in the Learning Media course for the group of students given the generative learning model are higher than the group of students given the expository learning model. In the group of students who had a negative attitude, the learning outcomes of the Learning Media course for the group of students given the generative learning model were lower than the group of students given the expository learning model. ABSTRAKPenelitian ini bertujuan untuk mengukur sejauh mana Pengaruh Model Pembelajaran Generatif Terhadap Hasil Belajar Mahasiswa Berdasarkan Student’s Response Attitude Pada Mata Kuliah Media Pembelajaran Semester Ganjil Tahun Akademik 2023/2024. Metode yang digunakan adalah quasi-eksperimental dengan desain treatment by level 2 x 2. Hipotesis penelitian diuji dengan menggunakan analisis varian (ANAVA) dua jalur. Hasil penelitian diperoleh bahwa; hasil belajar antara kelompok mahasiswa yang diberikan model pembelajaran generatif lebih tinggi daripada kelompok mahasiswa yang diberikan model pembelajaran ekspositori serta terdapat pengaruh interaksi antara model pembelajaran dan sikap mahasiswa terhadap mata kuliah Media Pembelajaran terhadap hasil belajar mata kuliah Media Pembelajaran. Pada kelompok mahasiswa yang memiliki sikap positif, hasil belajar mata kuliah Media Pembelajaran kelompok mahasiswa yang diberikan model pembelajaran generatif lebih tinggi dari kelompok mahasiswa yang diberikan model pembelajaran ekspositori. Pada kelompok mahasiswa yang memiliki sikap negatif, hasil belajar mata kuliah Media Pembelajaran kelompok mahasiswa yang diberikan model pembelajaran generatif lebih rendah dari kelompok mahasiswa yang diberikan model pembelajaran ekspositori.